Microbiome and pathogen interaction with the immune system - Kogut, Michael H.; Lee, Annah; Santin, Elizabeth (Poultry science, 2020)
The intestinal tract harbors a diverse community of microbes that have co-evolved with the host immune system. Although many of these microbes execute functions that are critical for host physiology, the host immune system must control the microbial community so that the dynamics of this interdependent relationship is maintained. To facilitate host homeostasis, the immune system ensures that the microbial load is tolerated, but anatomically contained, while remaining reactive to microbial invasion. Although the microbiota is required for intestinal immune development, immune responses regulate the structure and composition of the intestinal microbiota by evolving unique immune adaptations that manage this high-bacterial load. The immune mechanisms work together to ensure that commensal bacteria rarely breach the intestinal barrier and that any that do invade should be killed rapidly to prevent penetration to systemic sites. The communication between microbiota and the immune system is mediated by the interaction of bacterial components with pattern recognition receptors expressed by intestinal epithelium and various antigen-presenting cells resulting in activation of both innate and adaptive immune responses. Interaction between the microbial community and host plays a crucial role in the mucosal homeostasis and health status of the host. In addition to providing a home to numerous microbial inhabitants, the intestinal tract is an active immunological organ, with more resident immune cells than anywhere else in the body, organized in lymphoid structures called Peyer’s patches and isolated lymphoid follicles such as the cecal tonsils. Macrophages, dendritic cells, various subsets of T cells, B cells and the secretory immunoglobulin A (IgA) they produce, all contribute to the generation of a proper immune response to invading pathogens while keeping the resident microbial community in check without generating an overt inflammatory response to it. IgA-producing plasma cells, intraepithelial lymphocytes, and γδT cell receptor-expressing T cells are lymphocytes that are uniquely present in the mucosa. In addition, of the γδT cells in the intestinal lamina propria, there are significant numbers of IL-17-producing T cells and regulatory T cells. The accumulation and function of these mucosal leukocytes are regulated by the presence of intestinal microbiota, which regulate these immune cells and enhance the mucosal barrier function allowing the host to mount robust immune responses against invading pathogens, and simultaneously maintains immune homeostasis.